Structure and gas transport characteristics of triethylene oxide‐grafted polystyrene‐b‐poly(ethylene‐co‐butylene)‐b‐polystyrene. Issue 18 (1st August 2020) - Tian, Ding; Alebrahim, Taliehsadat; Kline, Gregory K.; Chen, Liwen; Lin, Haiqing; Bae, Chulsung
Abstract: Polymeric membrane‐based gas separation technology has significant advantages compared with traditional amine‐based CO2 separation method. In this work, SEBS block copolymer is used as a polymer matrix to incorporate triethylene oxide (TEO) functionality. The short ethylene oxide segment is chosen to avoid crystallization, which is confirmed by differential scanning calorimetry and wide‐angle X‐ray scattering characterizations. The gas permeability results reveal that CO2 /N2 selectivity increased with increasing content of TEO functional group. The highest CO2 permeability (281 Barrer) and CO2 /N2 selectivity (31) were obtained for the membrane with the highest TEO incorporation (57 mol%). Increasing the TEO content in these copolymers results in an increase in CO2 solubility and a decrease in C2 H6 solubility. For example, as the grafted TEO content increased from 0 to 57 mol%, the CO2 solubility and CO2 /C2 H6 solubility selectivity increased from 0.72 to 1.3 cm 3 (STP)/cm 3 atm and 0.47 to 1.3 at 35°C, respectively. The polar ether linkage in TEO‐grafted SEBS copolymers exhibits favorable interaction with CO2 and unfavorable interaction with nonpolar C2 H6, thus enhancing CO2 /C2 H6 solubility selectivity. Abstract : SEBS block polymer is grafted with a tunable amount of triethylene oxide (TEO) to impart CO2 permselectivity properties. The short TEO content is chosen to avoid crystallization, and the differential scanning calorimetry and X‐ray scattering results confirm the amorphous state of the membrane at room temperature. The CO2 /N2 selectivity increases with increasing content of the TEO group. The highest CO2 permeability (281 Barrer) and CO2 /N2 selectivity (31) are obtained for the membrane with the highest TEO content (57 mol%).